TRANSFORMATION OF TOURISM DESTINATIONS: OVERCOMING THE CHALLENGES OF THE CRISIS TOWARDS SUSTAINABILITY - Ricky Agusiady; Farida Yuliaty; Zaenal Aripin (Journal of Jabar Economic Society Networking Forum, 2024)
The tourism industry is faced with various challenges, including global crises such as the Covid-19 pandemic, which has significantly disrupted tourism activities. Transforming tourist destinations is the key to overcoming the challenges of this crisis towards the sustainability of the tourism industry. This research aims to analyze tourism destination transformation strategies in facing crisis challenges and promoting the sustainability of the tourism industry. The research method used in this research is qualitative, by conducting a literature review and analysis of various case studies regarding the transformation of tourist destinations. The research results show that the transformation of tourist destinations can successfully overcome crisis challenges by implementing strategies such as tourism product innovation, use of information and communication technology, environmental and cultural heritage preservation, empowerment of local communities, and collaboration between stakeholders.